The Warsaw underground : a memoir of resistance, 1939 - 1945 - Rosiński, Jan 1917-2012 (McFarland, 2014)
"The German invasion of Poland in September 1939 abruptly ended author Jan Rosinski's student life, and propelled him into an activist if not leadership role in the Polish resistance organization, Armia Krajowa or AK. In short order he became a talented forger of Nazi documents, especially travel papers that allowed many refugees to escape the city"..